A control banding method for chemical risk assessment in occupational settings in France - Aachimi, Abir; Marc, Florian; Bonvallot, Nathalie; Clerc, Frederic (Frontiers in Public Health, 2023)
Background This study describes a method whose aim is to help companies assess the chemical occupational risks related to labeled products and industrial chemical emissions. The method is intended to be used by industrial hygienists at the scale of one company. Both inhalation and cutaneous exposure routes are taken into account. Methods The method relies on a control-banding scheme. A work situation is described by exposure parameters such as the process or the local exhaust ventilation and by the hazard of the product. Each possible value of the parameters is associated with a “band,” which is associated with an integer value. The multiplication of these values results in a score, which represents a priority for intervention. The higher the score, the more the situation warrants investigation for implementing prevention measures, such as chemical substitution and the addition of local exhaust ventilation. To simplify communication, the priority is associated with a colored priority band: red for “very high priority,” orange for “high priority,” and green for “moderate priority.” The priority bands are computed for all work situations performed in a company. Results An example of the use of this method is described in a French façade insulation company. Conclusion A tool named Seirich was developed to implement this method and promote good practices for helping industrial hygienists in the prioritization of interventions for reducing chemical risk in France.